Предмет: Алгебра, автор: ілллюсик

обчислити: ∛(5√2-7)⋅√(3+2√2)

Ответы

Автор ответа: Dимасuk
15
∛(5√2 - 7)⋅√(3 + 2√2) = -∛(7 - 5√2)⋅√(2+ 2√2 + 1) = -∛(7 - 5√2)⋅√(√2 + 1)² = ... (1) 
a³ - 3a²b + 3ab² - b³ = 7 - 5√2
Подбором находим числа а и b:
a = 1; b = √2. 
1 - 3√2 + 6 - 2√2 = 7 - 5√2
(1) = -∛(1 - √2)³(√2 + 1) = -(1 - √2)(√2 + 1) = (√2 - 1)(√2 + 1) = 2 - 1 = 1.
Ответ: 1. 
Автор ответа: sedinalana
3
 \sqrt[3]{( \sqrt{2}-1)^3 } * \sqrt{( \sqrt{2} +1)^2} =( \sqrt{2} -1)*| \sqrt{2} +1|=( \sqrt{2} -1)( \sqrt{2} +1)=( \sqrt{2} )^2-1^2=2-1=1
Похожие вопросы